2017
DOI: 10.1177/0960327117710535
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and copy number variation analyses of human embryonic stem cell–derived neuroprogenitors after low-dose decabromodiphenyl ether and/or bisphenol A exposure

Abstract: The polybrominated diphenyl ether flame retardants decabromodiphenyl ether (BDE-209) and bisphenol A (BPA) are environmental contaminants that can cross the placenta and exert toxicity in the developing fetal nervous system. Copy number variants (CNVs) play a role in a number of genetic disorders and may be implicated in BDE-209/BPA teratogenicity. In this study, we found that BDE-209 and/or BPA exposure decreased neural differentiation efficiency of human embryonic stem cells (hESCs), although there was a >90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…It was found that decabromodiphenyl ether (BDE-209) and bisphenol A decreased DNA methylation and reduced DNA methyltransferase (DNMTI and DNMT3A) expression in human embryonic stem cells. 29 Moreover, it was shown that TDCIPP exposure predominantly resulted in hypomethylation of positions outside of CpG islands and within intragenic (exon) regions of the zebrafish genome. 30 Aberrant DNA methylation patterns were also present in human sperm when the exposure to OPFRs was increased.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that decabromodiphenyl ether (BDE-209) and bisphenol A decreased DNA methylation and reduced DNA methyltransferase (DNMTI and DNMT3A) expression in human embryonic stem cells. 29 Moreover, it was shown that TDCIPP exposure predominantly resulted in hypomethylation of positions outside of CpG islands and within intragenic (exon) regions of the zebrafish genome. 30 Aberrant DNA methylation patterns were also present in human sperm when the exposure to OPFRs was increased.…”
Section: Discussionmentioning
confidence: 99%
“…PBDE‐209 causes copy number variants at the different regions on chromosomes. The demethylation activity by PBDE‐209 collapses genomic stability at the embryonic stage that may affect neurodevelopment (Du, Sun, et al, 2018). Another in vivo study using rat hippocampal neurons exposed to PBDE‐209 showed the increased apoptosis with improved P38 MAPK level and oxidative stress besides global DNA hypomethylation (J. Chen, Liufu, Sun, Sun, & Chen, 2010).…”
Section: Epigenetic Changes Link Ecs To Adverse Health Outcomesmentioning
confidence: 99%
“…TCC is able to bioaccumulate into the human tissues, for instance, maternal and umbilical cord sera, urine, toe and fingernails, as well as hypothalamus and white matter in the human brain, threatening the safety of human (Pycke et al, 2014;Van Der Meer et al, 2017;Wei et al, 2017). TCC is a novel endocrine disruptor (Chung, Genco, Megrelis, & Ruderman, 2011) and also exacerbates pathophysiological conditions of the central nervous system (CNS), including traumatic injury, stroke, neurodegenerative diseases, autoimmune inflammation (Lee & McEwen, 2001;Wise, 2002 development (Du, Sun, et al, 2018). Another in vivo study using rat hippocampal neurons exposed to PBDE-209 showed the increased apoptosis with improved P38 MAPK level and oxidative stress besides global DNA hypomethylation (J. Chen, Liufu, Sun, Sun, & Chen, 2010).…”
Section: Triclocarbanmentioning
confidence: 99%
“…Neurons in the CA3 region of the hippocampus of these rats were also found to be undergoing significantly increased rates of apoptosis, with chromatin condensed and localized to the nuclear membrane [64]. Most recently, it was reported that BDE-209 exposures reduced hESC differentiation (although total induction was still greater than 90%) and also led to chromosomal copy number variants (CNVs), as well as decreased expression of DNMT1/3A [65].…”
Section: Relation Of Pbdes To Human Healthmentioning
confidence: 99%